Entrepreneurial orientation, business performance, and traditional leadership style - Chichi Andriani; Mega Asri Zona; Ilham Thaib (Cogent Business & Management, 2024)
This study aims to determine the role of entrepreneurial orientation in mediating Minangkabau Universal Leadership and the performance of Small and Medium Enterprises (SMEs) in Padang, West Sumatra, Indonesia. Minangkabau Universal Leadership is used as an antecedent to represent traditional type leadership in West Sumatra that consists of three values: custom, religious, and intellectual. This leadership type was found more suitable to implement in this research because West Sumatra is a unique province with an esteemed culture that is still used and held by its people nowadays. During the pandemic era (in 2020), there were lots of new businesses in a small and medium scale that were established in Padang, West Sumatra, Indonesia. Based on purposive sampling techniques, this study uses 180 small and medium businesses as a sample. The criteria of respondents are based on the type of business, the ownership, number of employees, year of establishment, and profit in a year. The data was collected through questionnaires from 2021 to 2022. Each of the businesses is represented by a respondent. After the hypotheses were tested using SEM-PLS, the study found that Minangkabau Universal Leadership has a positive and significant influence on business performance. Hence, entrepreneurial orientation was found to mediate the relationship between Minangkabau Universal Leadership and business performance.
Keywords: 650; Traditional leadership; entrepreneurial orientation; business performance